Samuelson's fallacy of large numbers with decreasing absolute risk aversion - Karl Whelan (University College Dublin, UCD School of Economics, 2024)
Samuelson (1963) conjectured that accepting multiple independent gambles you would reject on a stand-alone basis violated expected utility theory. Ross (1999) and others presented examples where expected utility maximizers would accept multiple gambles that would be rejected on a stand-alone basis once the number of gambles gets large enough. We show that a stronger result than Samuelson's conjecture applies for DARA preferences over wealth. Expected utility maximizers with DARA preferences have threshold levels of wealth such that those above the threshold will accept N positive expected value gambles while those below will not and these thresholds are increasing with N.
Keywords: D81; 330; Risk aversion; Paul Samuelson; Law of large numbers